Seasonal changes in the mycorrhizal symbiosis of Rhododendron tomentosum Harmaja in the Ukrainian Polissia - Nataliia Bielova (Інтродукція Рослин)
This study focuses on the mycorrhizal associations of Rhododendron tomentosum Harmaja with ericoid mycorrhizal fungi, typical for species in the Ericaceae family. The development of these symbiotic relationships varies seasonally and by habitat. Mycorrhizal colonization was studied across different phenological stages in natural populations of R. tomentosum in the Bilokorovytsky forestry, Zhytomyr region (Ukraine). Samples were taken at four stages of the growing season, analyzed morphologically, and quantitatively assessed. The results revealed that colonization peaks at the beginning and end of the vegetation period while declining during flowering and seed maturation. Additionally, we observed both ericoid mycorrhizae and dark septate endophytes (DSE) coexisting within the roots, suggesting that the symbiotic relationship is complex and influenced by multiple factors. These findings contribute to a deeper understanding of mycorrhizal dynamics in R. tomentosum and highlight the need for further research on seasonal and environmental influences on these associations.